Block by block: Building on our knowledge to better care for LGBTQIA+ patients. Issue 1 (23rd June 2022) - Driver, Lachlan; Egan, Daniel J.; Hsiang, Elaine; Lall, Michelle D.; Moll, Joel; Ritchie, Amanda M.; Sonn, Brandon J.; Totten, Vicken Y.; Williams, Dustin B.; McGregor, Alyson J.
Abstract: Background: Emergency physicians need to recognize the diversity of identities held by sexual and gender minorities, as well as the health implications and inequities experienced by these communities. Identities such as lesbian, gay, bisexual, transgender, queer, questioning, intersex, asexual, aromantic, and many others fall under the LGBTQIA+ acronym. This wide spectrum is seldom discussed in emergency medicine but nonetheless impacts both patient care and patient experience in acute and critical care settings. Aims: This commentary aims to provide a brief but nonexhaustive review of LGBTQIA+ identities and supply a critical framework for applying this understanding to patient encounters in the emergency department, as well as describe the challenges and educational aims at the level of medical school, residency, and postresidency. Materials and Methods: The commonly used and widely accepted definitions of LGBTQIA+ terms are described, as well as implications for patient care and emergency physician education. The authors of this writing group represent the Society for Academic Emergency Medicine, LGBTQ Task Force of the Academy of Diversity Inclusion in Medicine. Results: LGB terms are addressed, with LGBTQIA+ adding "intersex, " "asexual, " and "+, " to include other gender identities and sexual orientations which are not already included. This paper also addresses the terms "transition, " "nonbinary, " "polyamorous." "two‐spirit, " "queer, " and others. These acronyms and terms continually expand and evolve in the pursuit of inclusivity. Additionally, with some health issues potentially related to medications, hormones, surgery, or to internal or external genitalia, important EM physician tools include gathering an "organ inventory, " asking about sexual history, and conducting a physical exam. Discussion: Most persons have congruent biological sex, gender identity, and attraction to the "opposite" gender. However, humans can have every imaginable variation and configuration of chromosomes, genitalia, gender identities, sexual attractions, and sexual behaviors. Terms and definitions are constantly changing and adapting; they may also vary by local culture. Obtaining relevant medical history, conducting an "organ inventory, " asking about sexual history in a nonjudgmental way, and conducting a physical exam when warranted can all be important in delivering best possible medical care. Although there has been increased focus on education at the medical school, residency, and faculty level on LGBTQIA+ patient care in the ED, much work remains to be done. Conclusion: Emergency physicians should feel confident in providing a model of care that affirms the sexual and gender identities of all the patient populations we serve. Optimal patient‐centric care requires a deeper understanding of the patient's biology, gender identity, and sexual behavior encapsulated into the ever‐growing acronym LGBTQIA+.